Design, Synthesis, and Bioactivities of Novel Trifluoromethyl Pyrimidine Derivatives Bearing an Amide Moiety - Lan, Wenjun; Tang, Xuemei; Yu, Jia; Fei, Qiang; Wu, Wenneng; Li, Pei; Luo, Heng (Frontiers in Chemistry, 2022)
Twenty-three novel trifluoromethyl pyrimidine derivatives containing an amide moiety were designed and synthesized through four step reactions and evaluated for their antifungal, insecticidal, and anticancer properties. Bioassay results indicated that some of the title compounds exhibited good in vitro antifungal activities against Botryosphaeria dothidea (B. dothidea), Phompsis sp., Botrytis cinereal (B. cinerea), Colletotrichum gloeosporioides (C. gloeosporioides), Pyricutaria oryzae (P. oryzae), and Sclerotinia sclerotiorum (S. sclerotiorum) at 50 μg/mL. Meanwhile, the synthesized compounds showed moderate insecticidal activities against Mythimna separata (M. separata) and Spdoptera frugiperda (S. frugiperda) at 500 μg/mL, which were lower than those of chlorantraniliprole. In addition, the synthesized compounds indicated certain anticancer activities against PC3, K562, Hela, and A549 at 5 µg/mL, which were lower than those of doxorubicin. Of note, this work is the first report on the antifungal, insecticidal and anticancer activities of trifluoromethyl pyrimidine derivatives bearing an amide moiety.